2006
DOI: 10.1016/j.cmet.2006.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The DHR96 nuclear receptor regulates xenobiotic responses in Drosophila

Abstract: Exposure to xenobiotics such as plant toxins, pollutants, or prescription drugs triggers a defense response, inducing genes that encode key detoxification enzymes. Although xenobiotic responses have been studied in vertebrates, little effort has been made to exploit a simple genetic system for characterizing the molecular basis of this coordinated transcriptional response. We show here that approximately 1000 transcripts are significantly affected by phenobarbital treatment in Drosophila. We also demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
220
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(234 citation statements)
references
References 62 publications
11
220
3
Order By: Relevance
“…Consistent with this, we found that DHR96 is expressed in the region of the larval midgut, where npc1b exerts its functions ( Fig. 4A; King-Jones et al 2006;Voght et al 2007). This overlap in DHR96 and npc1b expression also appears to be functionally significant because specific expression of wild-type DHR96 in the midgut of DHR96 mutants is sufficient to restore appropriate npc1b transcriptional repression in response to cholesterol (Fig.…”
Section: Dhr96 Mutants Accumulate Cholesterolsupporting
confidence: 71%
See 2 more Smart Citations
“…Consistent with this, we found that DHR96 is expressed in the region of the larval midgut, where npc1b exerts its functions ( Fig. 4A; King-Jones et al 2006;Voght et al 2007). This overlap in DHR96 and npc1b expression also appears to be functionally significant because specific expression of wild-type DHR96 in the midgut of DHR96 mutants is sufficient to restore appropriate npc1b transcriptional repression in response to cholesterol (Fig.…”
Section: Dhr96 Mutants Accumulate Cholesterolsupporting
confidence: 71%
“…Thus, it is likely that the DHR96 mutants suffer from additional metabolic defects beyond their inability to properly regulate npc1b transcription. This conclusion is supported by the widespread effects of the DHR96 mutation on the expression of genes involved in lipid metabolism and midgut physiology, as well as the expression of DHR96 in tissues outside the midgut (King-Jones et al 2006). Further studies of DHR96 mutants should help to uncover its other key metabolic activities.…”
Section: Dhr96 Mutants Accumulate Cholesterolmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, we tested media containing another compound, phenobarbital (PB), to examine whether responses were specific to caffeine or of a more general nature. Like caffeine, PB is a potent inducer of detoxification responses in the fly, 37 but its biological activity is based on a different mechanism, because PB acts by stimulating GABA receptors. We then scored for obvious phenotypes (morphological changes and lethality) on either media type.…”
Section: Resultsmentioning
confidence: 99%
“…Approaches, such as sex-specific expression of P450s, induction capacity of P450s by various exogenous compounds, and transcriptional profiling have been useful in characterizing P450 functions (39)(40)(41)(42). In an effort to distinguish P450s with essential endogenous functions from those involved in detoxification, we characterized expression patterns of D. melanogaster P450s by in situ hybridization and performed a P450 RNA interference (RNAi) knockdown screen.…”
mentioning
confidence: 99%